Prais-Winsten algorithm for regression with second or higher order autoregressive errors - Dimitrios V. Vougas (Econometrics, 2021)
There is no available Prais-Winsten algorithm for regression with AR(2) or higher order errors, and the one with AR(1) errors is not fully justified or is implemented incorrectly (thus being inefficient). This paper addresses both issues, providing an accurate, computationally fast, and inexpensive generic zig-zag algorithm.
Keywords: 330; autoregressive errors; exact NLS; fast zig-zag algorithm; linear regression; Prais-Winsten algorithm; unconditional ML